Perbandingan Hasil Belajar Sebelum dan Setelah Menggunakan Metode SQ Pada Kemampuan Membaca Al Qur’an Peserta Didik Rumah Mungil - Adam Raihan Ansory; Luqman Abdul Jalal (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
This research was motivated by a gap in Al-Qur'an reading abilities, specifically in tajweed accuracy and vowel (harakat) consistency among students. This phenomenon demands innovative learning methods that are more measurable and practical. This study aims to determine the comparison of Al-Qur'an reading learning outcomes before and after the implementation of the Simulator Qiro?ah (SQ) method at Rumah Mungil. The type of research used is quantitative with a pre-experimental design through a one-group pre-test post-test approach. The research subjects consisted of 30 students at the Pra-Tahsin level, selected using a total sampling technique. Data collection was carried out through Al-Qur'an reading ability tests using assessment instruments based on SQ Standard Operating Procedures (SOP). Data analysis was conducted in two stages: descriptive statistical analysis and inferential statistical analysis using the Wilcoxon Signed Rank Test non-parametric test assisted by SPSS 25 software, as the data were not normally distributed (Sig. 0.000 < 0.05). Descriptive results showed a significant increase in the mean value, from 52.83 at the pre-test to 72.20 at the post-test. Inferentially, the hypothesis testing results showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, meaning that is rejected and is accepted. Thus, it can be concluded that there is a significant difference in students' Al-Qur'an reading ability before and after the implementation of the Simulator Qiro?ah (SQ) method. The application of the SQ method through a beat-based approach is proven to provide a positive contribution to improving the quality and standards of students' Al-Qur'an recitation at Rumah Mungil.